2019
DOI: 10.3889/oamjms.2019.077
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Function and Its Related Potentials in Children with Beta Thalassemia Major: An Egyptian Study

Abstract: BACKGROUND: Repeated blood transfusions and hemolysis in β-Thalassemia major children lead to iron overload in various organs, including the brain which may cause neurodegeneration. AIM: To evaluate intelligence quotient in children with β-thalassemia major and healthy counterparts and to assess risk factors that cause cognitive problems. SUBJECTS AND METHODS: This case-control study was performed on 50 children aged 6-16 years old with β-thalassemia major as patients group and compared with 50 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
5
11
1
Order By: Relevance
“…Because of iron overload, patients may have complications in different organs, including endocrinopathies, heart failure, conduction abnormalities, liver derangement, and splenomegaly, which requires splenectomy [9]. Recent data suggested a possible link between neurotransmitter abnormalities in thalassemia patients and the occurrence of depression [27][28][29][30]. Our results showed higher scores in all three domains in patients' receiving deferoxamine compared to oral chelators, but the difference did not reach a statistical significance.…”
Section: Discussioncontrasting
confidence: 55%
“…Because of iron overload, patients may have complications in different organs, including endocrinopathies, heart failure, conduction abnormalities, liver derangement, and splenomegaly, which requires splenectomy [9]. Recent data suggested a possible link between neurotransmitter abnormalities in thalassemia patients and the occurrence of depression [27][28][29][30]. Our results showed higher scores in all three domains in patients' receiving deferoxamine compared to oral chelators, but the difference did not reach a statistical significance.…”
Section: Discussioncontrasting
confidence: 55%
“…Diseases, such as sickle-cell anaemia, beta thalassaemia minor, iron-deficiency anaemia and chronic obstructive pulmonary disease, that are also characterized by chronic hypoxia have been associated with cognitive dysfunction (Pollitt, 1993;Stuss et al, 1997;Lozoff et al, 2006;McCann & Ames, 2007;Nevruz et al, 2007;Khedr et al, 2008;Vichinsky et al, 2010;Cichowitz et al, 2014;Mackin et al, 2014;DeBaun & Kirkham, 2016), but data pertaining to TDT b-TM is limited. Notably, the few existing studies of cognitive function in b-TM were done almost exclusively on children and adolescents Karimi et al, 2006;Shehata et al, 2010Shehata et al, , 2012Duman et al, 2011;Raafat et al, 2014;El-Alameey et al, 2019). To our knowledge, only three studies have assessed cognitive function in adults with b-TM (Monastero et al, 2000;Raz et al, 2016aRaz et al, ,2016b, showing marked reduction in cognitive performance in those patients when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Metafratzi et al (2001) reported that, in patients with β-TM, increased iron deposition may be observed in the putamen, caudate nucleus, and motor and temporal cortex, which are important for cognitive functions including implicit and explicit memory [58]. The damage to the nervous system in those patients may be attributed to many factors acting as cumulative minor injuries over many years including hemolysis and repeated blood transfusions, which lead to a decrease in nitric oxide levels and IO in the brain [59]. The latter, in turn, may lead to oxidative stress aggravating brain tissue damage [60].…”
Section: Discussionmentioning
confidence: 99%